2016
DOI: 10.2337/db16-0039
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Resistance, Microbiota, and Fat Distribution Changes by a New Model of Vertical Sleeve Gastrectomy in Obese Rats

Abstract: Metabolic surgery improves insulin resistance and type 2 diabetes possibly because of weight loss. We performed a novel sleeve gastrectomy in rats that resects ∼80% of the glandular portion, leaving the forestomach almost intact (glandular gastrectomy [GG]) and compared subsequent metabolic remodeling with a sham operation. GG did not affect body weight, at least after 10 weeks; improved hepatic and peripheral insulin sensitivity likely through increased Akt, glycogen synthase kinase 3, and AMPK phosphorylatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 41 publications
5
40
0
Order By: Relevance
“…In this work we investigated the effect of HFD, VSG (accompanied by dietary switch or not) and change of diet alone on the Sprague-Dawley rat cecal microbiota, a follow-up of our earlier work reporting on weight loss results [18]. The combined effect of diet and surgery had distinctive effects on the microbiota in line with previous reports [8,28,30]. In addition to this, an obvious effect attributable to pre-operative antibiotic prophylaxis is noted, reflected in the effects observed in the Shamoperated cohort of this study.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…In this work we investigated the effect of HFD, VSG (accompanied by dietary switch or not) and change of diet alone on the Sprague-Dawley rat cecal microbiota, a follow-up of our earlier work reporting on weight loss results [18]. The combined effect of diet and surgery had distinctive effects on the microbiota in line with previous reports [8,28,30]. In addition to this, an obvious effect attributable to pre-operative antibiotic prophylaxis is noted, reflected in the effects observed in the Shamoperated cohort of this study.…”
Section: Discussionsupporting
confidence: 59%
“…Nevertheless, we observed a pronounced reduction that persisted after the switch of diet alone. Alpha diversity was also affected by VSG, but to a lesser degree than by the change of diet, although VSG only removes the glandular part of the stomach and leaves the intestine intact [28]. Nonetheless, both C and D groups subjected to VSG had reduced alpha diversity, similar to what has been seen in humans and animals [41,42], but also to Sham surgery, suggesting the effects of the antibiotic Enrofloxacina were the primary cause rather than the surgery itself.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…However, except for BAT index, GF group significantly decreased the indices of liver, lung, kidney, muscle and EFP than the SPF group. Basso et al demonstrated the gut microbiota can increase body fat 16. D'Aversa et al also showed that the gut microbiota not only promotes lipogenesis and VLDL production, it also facilitates storage in adipose tissue by increasing LPL activity 17.…”
Section: Results and Commentsmentioning
confidence: 99%
“…Persisting post-surgery microbiota changes suggest adaptation to anatomic and physiologic changes, such as reduced acid production, increased oxygen content, altered bile acid concentrations delivered to the colon, induced by the surgery. Previously reported effects of bariatric surgery on microbiota diversity have ranged from an increase in total diversity 25, 26 to absence of change and even a decrease in alpha diversity 27 . We suspect that baseline sampling in relation to crash diet may vary between studies, and might contribute to the reported differences between studies.…”
Section: Discussionmentioning
confidence: 99%